Kallikrein‐related peptidase 4 induces cancer‐associated fibroblast features in prostate‐derived stromal cells. Issue 10 (10th August 2017) - Kryza, Thomas; Silva, Lakmali M.; Bock, Nathalie; Fuhrman‐Luck, Ruth A.; Stephens, Carson R.; Gao, Jin; Samaratunga, Hema; ,; Lawrence, Mitchell G.; Hooper, John D.; Dong, Ying; Risbridger, Gail P.; et al.
Abstract : The reciprocal communication between cancer cells and their microenvironment is critical in cancer progression. Although involvement of cancer‐associated fibroblasts (CAF) in cancer progression is long established, the molecular mechanisms leading to differentiation of CAFs from normal fibroblasts are poorly understood. Here, we report that kallikrein‐related peptidase‐4 (KLK4) promotes CAF differentiation. KLK4 is highly expressed in prostate epithelial cells of premalignant (prostatic intraepithelial neoplasia) and malignant lesions compared to normal prostate epithelia, especially at the peristromal interface. KLK4 induced CAF‐like features in the prostate‐derived WPMY1 normal stromal cell line, including increased expression of alpha‐smooth muscle actin, ESR1 and SFRP1 . KLK4 activated protease‐activated receptor‐1 in WPMY1 cells increasing expression of several factors (FGF1, TAGLN, LOX, IL8, VEGFA) involved in prostate cancer progression. In addition, KLK4 induced WPMY1 cell proliferation and secretome changes, which in turn stimulated HUVEC cell proliferation that could be blocked by a VEGFA antibody. Importantly, the genes dysregulated by KLK4 treatment of WPMY1 cells were also differentially expressed between patient‐derived CAFs compared to matched nonmalignant fibroblasts and were further increased by KLK4 treatment. Taken together, we propose that epithelial‐derived KLK4 promotes tumour progression by actively promoting CAF differentiation in the prostate stromal microenvironment. Abstract : The kallikrein‐related peptidase 4 (KLK4) is highly expressed in epithelial cells of the premalignant prostate (prostatic intraepithelial neoplasia). Prostate epithelial‐derived KLK4 activates protease‐activated receptor‐1 in prostate‐derived stromal fibroblast cells to induce a cancer‐associated phenotype. KLK4 induces the cancer‐associated phenotype in patient‐derived normal prostate stromal fibroblasts.